Epigenetics of Osteoporosis: Critical Analysis of Epigenetic Epidemiology Studies - A. Riancho, José (Current Genomics, 2015)
Osteoporosis is a systemic disease characterized by low bone mass and microarchitectural deterioration of bone tissue, with a consequent increase in bone fragility and propensity to fracture. Environmental factors during early life, including those in utero, may influence bone mass during later life and, consequently, the risk of osteoporosis. Epigenetic mechanisms play central roles in the differentiation of bone cells, osteoblasts and osteoclasts, responsible for bone formation and bone resorption, respectively. A few studies have shown some differentially methylated genes in patients with osteoporosis. They include genes belonging to the Wnt pathway, which is an important regulator of osteoblast differentiation, and other genes involved in the development of the skeleton. Likewise, some miRNAs may be differentially expressed in these patients. However, those preliminary results need to be replicated in other cohorts. Unlike the genome, the epigenome is cell-specific and changes with aging and environmental factors. Therefore, the design and interpretation of epigenetic epidemiology studies pose a number of practical difficulties. A framework for the critical appraisal of these studies is proposed.
Keywords: DNA methylation